2012
DOI: 10.4028/www.scientific.net/amr.518-523.5734
|View full text |Cite
|
Sign up to set email alerts
|

Retrievals of Aerosol Optical Depth and Angstrom Exponent for Identification of Aerosols at Kuching, Sarawak

Abstract: Anthropogenic and natural aerosols are important atmospheric constituents that significantly contribute to the Earth’s radiation budget but remain uncertainties due to the poor understanding of aerosol properties and its direct effects on scattering and absoprtion of solar radiation and the ability of aerosols to stay in atmosphere for a very short time. Different types of aerosols, representing biomass burning, urban or continental aerosols, maritime aerosols and dust particles will give different characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…(2002bSmirnov at al. ( , 2003, Pace et al (2006), Kaskaotis et al (2007), Toledano et al (2007), Salinas et al (2009), andJalal et al (2012) were used to distinguish the aerosol types. The testing results indicate that the threshold criteria by Toledano et al (2007) were the most reliable, because of the minimal occurrence value of the indistinguishable aerosols (referred as mixed-type aerosols, MIXA).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2002bSmirnov at al. ( , 2003, Pace et al (2006), Kaskaotis et al (2007), Toledano et al (2007), Salinas et al (2009), andJalal et al (2012) were used to distinguish the aerosol types. The testing results indicate that the threshold criteria by Toledano et al (2007) were the most reliable, because of the minimal occurrence value of the indistinguishable aerosols (referred as mixed-type aerosols, MIXA).…”
Section: Discussionmentioning
confidence: 99%
“…The aerosol types are seasonally discriminated from scatter plots of Ångström exponent against the AOD. Threshold values in the scatter plot for aerosol classification have been previously reported by Smirnov et al (2002bSmirnov et al ( , 2003, Pace et al (2006), Kaskaotis et al (2007), Toledano et al (2007), Salinas et al (2009), andJalal et al (2012). The data selection criteria proposed by Tan et al (2014a) are used in this study.…”
Section: Methodology and Statistical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As resulting by the occurrence of dry season which usually occurs during June until September yearly and also comes from haze episodes and also from urbanization. Study by [12] classified that In Kuching area dominant aerosols occurred in Kuching area urban and continental aerosols. It can be shown that at Julian Day 253 in 2015 there are extremely high value of AOD MODIS was retrieved with 6.0 while only 2.9 for AOD AERONET .…”
Section: Variations Of Aerosol Optical Depthmentioning
confidence: 99%